(untitled) (Fiep Bulletin - online, 2011)
The gestational period is a phase that determines biological, psychological, inter-relational and socio-cultural changes in the life of women, including diagnostic, preventive, curative and diet measures, aiming at the well-being and quality of life of the pregnant woman and her child. Quality of life is conceptualized by WHO as the perception of any person of his life position in the cultural context and value systems in order to respect their goals, expectations and concerns. Descriptive quantitative approach, addressing quality of life of a group of pregnant women in a Basic Health Unit in the city of Parnamirim/RN, in Northeast Brazil, with SUS attendance, considered low-risk pregnancy. Data collection occurred over a period of 4 months during the prenatal visits with 64 women in 2008. It was identified that these women consider important for a good quality of life in pregnancy: health, food, family, partner, housing, sleep, leisure, and which could harm their quality of life: domestic violence, overwork, disease, financial hardship; homelessness and little sleep. Reported well-received prenatal and scored: clarification on the baby’s healthmedical and nurse consultation, answering questions, guidance on labor and delivery, postpartum and breastfeeding, and what matters most in the prenatal care is test requests, answering questions and physical examination. These results mean that the concept of quality of life for these women should be related to humanization. It is necessary that the quality of care in health services should be composed of technical competence, ability to interact and that complaints and discomforts of these users are resolved, or at least minimized, when they are heard, understood, respected, welcomed and considered by all health professionals that are attending.